Determination of rubella virus antibodies in pregnant women referring to Kerman Maternity Hospitals in 1999 - T Ashraf Ganjoei; MM Mohammadi (JRI, 2001)
Rubella is a viral infection. If it occurs during pregnancy, it’s responsible for serious fetal problems. Thus identification and vaccination of sensitive women is very important. This study was done for identification of protective rubella antibody titer (15mIU/ml) in 410 women of maternity hospitals in Kerman city. They were selected among who referred to maternity hospitals in Kerman. Randomized blood samples were collected and evaluated for rubella virus antibodies by ELISA method. Data analysis was done by chi-square test, Fisher exact test and student t-test. Protective rubella antibody titer was positive in 94.6% and negative in only 5.4%. Negative antibody titer in working wives (11.5%) was more than housewives (4.3%) (p<0.05). There was no significant difference in presence of antibody in regard with age, job, resident place, history of vaccination against rubella and history of rubella infection in herself or her family. Despite of high percent of immunity against rubella among women, it seems protection against it, is not enough. Therefor national vaccination plan was recommended for young women and adults which are not pregnant, or have no plan for getting pregnant 3 months after vaccination, and those who have low immunity against rubella.
Keywords: Antibody titer, Pregnant women, Vaccination